Numerical modeling of interply adhesion in composite forming of viscous discontinuous thermoplastic prepregs. (15th June 2020) - Mulye, P.D.; Hemmer, J.; Morançay, L.; Binetruy, C.; Leygue, A.; Comas-Cardona, S.; Pichon, P.; Guillon, D.
Abstract: "Quilted Stratum Process" (QSP®) is a new process in the category of thermoplastic composite forming with the objective to locally strengthen the composite parts by strategically stacking discontinuous UD/woven prepregs while maintaining the short cycle time of about 1 min. Interply adhesion arising due to polymer tack plays an important role in QSP® due to the presence of resin-rich layer at the ply-ply interface, inability to use blank holders for prepreg patches and high temperature of forming process where the resin is in melt state. Without modeling interply adhesion in the numerical simulation of their forming, plies delaminate unrealistically without any resistance which in turn results in incorrect final positions of the prepreg patches. Thus, a penalty based, semi-empirical contact model for interply adhesion has been developed and implemented in the industrial finite element code of Altair RADIOSS™. This model allows sliding of plies over long distance while providing a finite adhesive strength before delamination. It requires minimal characterization for which a measurement method is proposed. The usage of this model in a full scale numerical simulation showed that the final ply positions were predicted with a much better accuracy. Also, the predictions of fibre orientations within individual plies are in good agreement with the experimental observations. Highlights: Proposed a numerical model for interply adhesion between molten thermoplastic prepregs for the Quilted Stratum Process (QSP®). Experimentally quantified the adhesive strength of melt PA-66 polymer which serves as the input to this numerical model . Performed a numerical simulation of QSP® on an industrial component in Altair RADIOSS™. Compared the final positions and fibre orientations of viscous discontinuous patches with actual part.